Design Optimization of Automotive Bumper Beam Through Energy Absorption Analysis - A, Hambali; A.R, Rabiatul; A.S, Rahim; S, Taufik (Universitas Malahayati Press, 2012)
An automotive bumper beam is a safety component with function to absorb energy during collision. It is important to continue improving the bumper beam design in order to increase the vehicle safety features. The aim of this paper is to investigate the impact behavior of original and new proposed bumper beam designs in low velocity impact. The new bumper beam material is substituted by SMC composite in order to reduce the weight of original bumper beam design. Three main factors have been taken into account in this study, which are the cross section of the bumper beam, strengthening ribs and the thickness. The energy absorption was analyzed using finite element analysis (FEA) approach. It was found that curved D cross section beam has appropriate energy absorption and deflection compares with the original bumper beam design and others new cross section designs.